DURABILITY AND MECHANICAL CHARACTERISTICS OF POLYMER MODIFIED FERROCEMENT IN STRUCTURAL DEVELOPMENT - Fahrizal Zulkarnain S.T., M.Sc., Ph.D; Mohd. Zailan Suleiman (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
This paper Discusses The Durability Study of Polymer-Modified Ferrocement In Comparison With Conventional Ferrorcement Particularly When Exposed To Severe Environmental Conditions. The Development Of Strength, Deformability And Fracture Properties Were Slightly Different From Conventional Ferrocement. Prepeak Load Region. Fracture Toughness And Deformability Increased Significantly. However, The Post Peak Behaviour Was Quite Similar To Conventional Ferrocement.